Geographic Difference of Mortality of Creutzfeldt-Jakob Disease in Japan - Nakamura, Yosikazu (J Epidemiol, 2006)
BACKGROUND: The geographic mortality difference of Creutzfeldt-Jakob disease is still unclear in Japan. METHODS: Using vital statistics of Japan for 6 year period between 1999 and 2004 officially published by the government, we observed the mortality from Creutzfeldt-Jakob disease (ICD-10th: A81.0 and A81.8) by prefecture. Standardized mortality ratios were calculated for the 47 prefectures. RESULTS: For the observed 6 years, a total of 792 deaths from Creutzfeldt-Jakob disease were observed whole in Japan. Two prefectures, Akita and Yamanashi, presented significantly high standardized mortality ratios. In addition, Tochigi, Kochi, and Nagasaki showed standardized mortality rates higher than 1.5 without significance. No prefecture had significantly low standardized mortality ratios. CONCLUSION: Some prefectures with high mortality rate from Creutzfeldt-Jakob disease existed in Japan. Some of them had high incidence rate in a survey conducted in 1996 as well.